Alternanthera brasiliana L. extract alleviates carbon tetrachloride-induced liver injury and fibrotic changes in mice: Role of matrix metalloproteinases and TGF-β/Smad axis. (1st March 2023) - Paliwal, Vinay M.; Kundu, Sourav; Kulhari, Uttam; Jala, Aishwarya; Ishteyaque, Sharmeen; Borkar, Roshan M.; Mugale, Madhav Nilakanth; Murty, Upadhyayula Suryanarayana; Sahu, Bidya Dhar
Abstract: Ethnopharmacological relevance: Alternanthera brasiliana L. is a flowering plant belonging to the family Amaranthaceae and is popularly known as "penicillin". It is used in folk medicine to treat infections, coughs, wound healing, and inflammatory diseases. Aim of the study : We investigated the effect of Alternanthera brasiliana L. leaves hydroalcoholic extract (AB) against oxidative stress, inflammation, and fibrotic changes in an experimental model of carbon tetrachloride (CCl4 )-induced liver injury and fibrosis in mice. Materials and methods: Thirty-six male Balb/C mice were randomized into five groups: normal control, AB control, CCl4 control, CCl4 + AB-200 mg/kg, and CCl4 + AB-400 mg/kg. In mice, liver injury was induced by intraperitoneal injection of CCl4 (20% in corn oil, 5 ml/kg body weight) thrice a week for six consecutive weeks. AB extract at two doses (200 mg/kg and 400 mg/kg body weight) was administered orally for six consecutive weeks. Liver injury-related serum markers (ALT, AST, ALP), antioxidants (GSH, GST, SOD, and vitamin C), pro-inflammatory cytokines including tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-18, ultrasonographic and histological alterations, proteins of matrix metalloproteinases (MMPs) and tissue inhibitors of matrix metalloproteinase-1 (TIMP-1), nuclear factor-κB (p65) (NF-κB), nod-like receptor protein 3 (NLRP3), and TGF-β/Smad signaling were accessed. LC-Q-TOF-MS/MS analysis of AB was performed. Results: AB treatment significantly decreased the CCl4 -induced rise in serum ALT, AST, and ALP activities and improved the histological alterations. Compared with the CCl4 -treated group, treatment with AB significantly restored the hepatic antioxidants and reduced the pro-inflammatory cytokines in the liver. The antioxidant activity of AB may be attributed to its terpenoid constituents, which was confirmed by LC-Q-TOF-MS/MS analysis. The CCl4 -induced rise in expression of MMP-2 and MMP-9 and decrease in TIMP-1 were markedly restored in the AB-treated groups. Further findings revealed a significant reduction in the protein levels of phospho–NF–κB (p65), NLRP3, TGF-β, pSmad2/3, collagen I, and α-smooth muscle actin (α-SMA) in the AB treatment groups. Conclusions: The hepatoprotective effect of AB may be attributed to the high content of terpenoid compounds and alleviates liver injury and associated fibrotic changes through modulating MMPs, NF-κB (p65), and the TGF-β/Smad axis. Graphical abstract: Image 1 Highlights: Alternanthera brasiliana extract (AB) exhibits hepatoprotective effect in mice. LC-Q-TOF-MS/MS analysis reveals terpenoids (38.7%) are major constituents in AB. AB restores antioxidants and reduces pro-inflammatory cytokines in the liver. AB treatment impedes the MMP2/MMP9/TIMP-1 and the TGF-β/Smad signaling axis.